Persiapan Dakwah dan Segenap Sarananya dalam kitab al-Qudwah Hasanah fi Manhaji al-Da’wah Ilallah; Kajian Dakwah berbasis Perencanaan Perspektif Konteks Kekinian - Mohammad Rofiq (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2022)
Preparation and development of facilities is a very important factor for the success of a da'wah agenda. Al-Quran is very important for Muslims to prepare a plan in every activity of life, especially in the field of da'wah. History of the Prophet Muhammad SAW very crowded with various locations in the Prophet Muhammad SAW and the accuracy of his planning in carrying out his agenda. Planning activities are an organized approach to dealing with da’wah problems in the community. This research uses library research method. The results of this study indicate that da'wah planning can bridge the gap between preachers and the goals they want to achieve. Planning can answer who, what, when, where, and how da'wah actions can be carried out properly